Peran AKDPP (Aliansi Kawal Demokrasi Pilkada Pati) dalam Kemenangan Kotak Kosong di Desa Gajahmati dan Desa Maitan pada Pilkada Kabupaten Pati Tahun 2017 - Puspitasari, Siti Dwi; Harsasto, Priyatno (Journal of Politic and Government Studies, 2018)
The issue with the empty box is already familiar with the elections in Indonesia, it is already done in some region. As an election in Pati Regency in 2017, it is known there is only one single candidate who involved. It makes the empty box as an opponent. Uniquely, in Pati Regency, people who unhappy with the incumbent are doing resistance with an action to select the empty box and called themselves as Alliance of Democracy Election Pati (AKDPP). The purpose of this research is to know how big the role of AKDPP in winning the empty box in Gajahmati and Maitan Villages in Pati election in 2017. The method that used in this research is a qualitative method with collecting observation data whether in interview and document study. The informants are volunteers of AKDPP and the parties concerned. The highest number of empty box vote in Gajahmati and Maitan Villages does not mean the entirely due to the role of AKDPP, they do have a role on the number of empty box votes that can be considered quite large in Pati election in 2017. However, the victory in Gajahmati and Maitan villages is not due to the role of AKDPP. Both villages each have different backgrounds and winning factors.Key words: Election, Opposition, Empty Box